Knitted fabrics design and manufacture: A novel CAD system for qualifying bagging performance based on geometric-mechanical models. (June 2016) - Mao, Aihua; Luo, Jie; Li, Yi; Lin, Yinglei; Han, Yanxia
Abstract: Knitted fabrics have excellent formability and tensile ability and are widely used in textile-related products and industrial applications. The traditional quality control on fabric's performance is undertaken by repeated measurement and testing which is very time-consuming and has great expense. There are urgent requirements for the designers and manufacturers to validate and control the mechanical performance of knitted fabrics. In this paper, we present a novel simulation-based CAD system for evaluating and qualifying the bagging performance of knitted fabrics. A set of geometric-mechanical models are developed with characterization of the fibers/yarns and fabrics for available inputs, which make it feasible for practical applications. Through encapsulating the models and presenting with a series of friendly interfaces, the CAD system offers users the abilities of data management, numerical design, bagging simulation and performance preview of knitted fabrics. The simulation capability of the models is validated by comparing the predicted results with measured data from experiments under same bagging testing conditions. The potential industrial applications of this system is demonstrated, and the designers and manufacturers can achieve the knitted fabric products with desirable mechanical functions effectively and economically. Highlights: Develop a novel CAD system to evaluate and qualify the bagging performance of knitted fabrics. Simulate the bagging rheological behaviors in knitted fabrics by a set of geometric-mechanical models. Characterize the parameters of fibers, yarns and fabrics provided with available measurement methods. Rapidly achieve the knitted fabric products with desirable mechanical functions.